Pelatihan Senam Pencegahan Osteoporosis dan Penyuluhan Kesehatan Gigi Mulut pada Masyarakat Pre dan Lanjut Usia Anggrek 3 - Astuti, Luki; Hanin, Isya; Aryadi; Tanjung, Rizki (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Living a healthy life as a senior is the desire of everyone. However, keeping an elderly healthy is not easy. There are many challenges to face, because the elderly are susceptible to a variety of diseases. As you age, your body undergoes many changes or aging processes, and the changes you feel cover the entire limb. Vascular problems such as hypertension and other heart problems are common. Not only that, the elderly are also at risk of suffering from bone diseases such as osteoporosis, which can be dangerous because it can result in bone fractures and inhibit the activity of the elders because they have to lie more. Osteoporosis is often associated with periodontitis, as both are diseases of the bone caused by inflammation and old age. Both osteoporosis and periodontitis have similar risk factors such as smoking, poor nutritional status, age and immune deficiency. Osteoporosis can be prevented by eating foods rich in calcium, avoiding smoking and alcoholic beverages, having regular and regular physical activity, and exposure to sufficient sunlight. Preventing osteoporosis can reduce the risk of periodontitis in the elderly. This community service (PkM) is held for the elderly living in Grand Depok City Depok Residential, West Java. It is hoped that these activities will raise awareness of the elderly in particular, and the general public of the importance of health. It is expected that osteoporosis gymnastics for the elderly can be performed on a regular basis at Posbindu Anggrek 3.